Microplastic pollution in Cynoscion spp, Opisthonema libertate and Mugil cephalus from the Tropical Eastern Pacific - Bailón Macías, Andrés Leonardo (2023)
Microplastics create serious problems in the seas, threatening marine life, polluting water and affecting ecosystems. Its accumulation and consumption by marine organisms has negative consequences throughout the food chain. Based on this, the present work evaluated the contamination by microplastics in Cynoscion spp, Opisthonema libertate and Mugil cephalus, species of high and low depth of the Eastern Tropical Pacific in Ecuador. Among the results obtained, the presence of shapes and colors of plastic polymers in M. cephalus captured at a shallow depth of up to 1.8 meters stands out. The presence of 449 units of plastic polymers was detected out of a total of 36 samples of M. cephalus, which represents an occurrence of 83%. In contrast, the lowest occurrence was 0% for Cynoscion spp and 6% for O. libertate, in deep drafts up to 9.1 meters deep. In shallow-draft species, the presence of microplastics may be related to their greater proximity to sources of pollution, such as urbanized coastal areas or intensive human activities. However, the absence of microplastics in deep-water species may indicate lower exposure or more efficient filtering capacity.